2011
DOI: 10.4103/0970-9290.84280
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported tobacco use, knowledge on tobacco legislation and tobacco hazards among adolescents in rural Kerala State

Abstract: The finding that tobacco consumption increases with age is a matter of concern. In addition to their clinical work, dental professionals should also educate the public on the hazards of tobacco and conduct tobacco cessation programmes for adolescent groups to control the tobacco epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…9 In present study consumers of tobacco products were 8% while current use of any form of tobacco was 11% in study of Kumar PM et al and 8% in the study of Jayakrishna et al 10,11 In the National GYTS (Global Youth Tobaaco Survey) 6 conducted in 2004 in India, the prevalence of ever tobacco use was found to be 25.1% whereas current tobacco use was found to be 17.5%.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…9 In present study consumers of tobacco products were 8% while current use of any form of tobacco was 11% in study of Kumar PM et al and 8% in the study of Jayakrishna et al 10,11 In the National GYTS (Global Youth Tobaaco Survey) 6 conducted in 2004 in India, the prevalence of ever tobacco use was found to be 25.1% whereas current tobacco use was found to be 17.5%.…”
Section: Discussionmentioning
confidence: 51%
“…[15][16][17] In present study, 70.5% students had correct knowledge regarding "Sale of tobacco products is prohibited below 18 years of age limit" while in the similar studies the proportion of correct knowledge was ranged from 13-25%. 11,12,16 In few of the studies conducted to know the attitude of the participants, 88-92% students support the "ban on public use of tobacco". 9,15 In the study of Ballal et al, 94.5% participants believed that sale of tobacco should not be allowed below 18 years of age and similar proportion was observed in other study conducted in Banglore.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,20,21 In a study by Jayakrishnan et al showed a high prevalence of smokeless tobacco use among school students (4.1%); with current smokers being less than 1% and also similar findings were noted by Sinha et al in a village of Bihar. 22,23 Tobacco products are socially sanctioned but are freely available in every nook and corner throughout the country. Trend toward smoking among the youths is increasing smoothly as reported by GYTS 2009 and Gajalakshmi et al 5,24 The public health implication of these habits starting at an early age is that it is well established fact that people change over from smokeless form to smoking over a time span, which sooner or later will form a threat and burden to the national and international health and economy.…”
Section: -11mentioning
confidence: 99%
“…Most of the earlier studies focused mainly on prevalence and practices of smoking among targeted populations such as school children, adolescents, students, professionals, etc. (Sinha et al, 2007;Saade et al, 2009;Khami et al, 2010;Jayakrishnan et al, 2011;Al-Naggar et al, 2012). Socio-demographic determinants might play a crucial role in smoking and its cessation.…”
mentioning
confidence: 99%